Letter from Ray E. Loehr to Members of the State Public Works Board - Ray E. Loehr:::::: (1978)
A letter to members of the State Public Works Board informing them of approved items regarding the development of Oxnard Community College. Includes information on the financials required to develop Oxnard Community College.